INTEGRATING BUDDHIST ETHICS AND SOCIAL HARMONY: A RELIGIOUS MODERATION FRAMEWORK INSPIRED BY THE NOBLE EIGHTFOLD PATH - Widiyanto Widiyanto; Euis Dewi Yuliana; Burmansah Burmansah (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to describe how local factors through a Buddhist approach influence the practice of religious moderation in the village of Rajabasa Lama, Labuhan Ratu District, East Lampung Regency, Lampung Province. The primary focus of this research is on the role of Buddhists in internalizing and implementing the four main pillars of religious moderation, namely commitment to nationalism, tolerance, anti-violence, and appreciation of local culture in the life of the village community. This study uses a qualitative approach with a phenomenological method. Data collection techniques involve participatory observation, in-depth interviews, and documentation studies. According to Colaizzi, the research procedure refers to the seven stages of phenomenology, while informants were selected using purposive sampling techniques. Data are analyzed through pattern matching, explanation making, and time series analysis. The research results show that Buddhist communities in the village of Rajabasa Lama have successfully implemented religious moderation by integrating the values of the Hasta Arya Marga teachings in Buddhism and the principles of multiculturalism in social life. National commitment, a sense of tolerance, anti-violence, and appreciation for their local culture are reflected in inclusive attitudes, active tolerance, and participation in interfaith activities without creating exclusive boundaries. This moderation process is formed through the practice of wisdom, morality, and concentration expressed in peaceful, ethical, and dialogical social discourse, thus strengthening a harmonious collective identity.